Advances in radiotherapy in bone metastases in the context of new target therapies and ablative alternatives: A critical review. (October 2021) - Gouveia, André G.; Chan, Dominic C.W.; Hoskin, Peter J.; Marta, Gustavo N.; Trippa, Fabio; Maranzano, Ernesto; Chow, Edward; Silva, Mauricio F.
Highlights: In uncomplicated BM, SF RT produces similar overall and complete response rates to MF, butit is associated with a higher retreatment rate. Complicated bone metastases can be defined as the presence of impending or existing pathologic fracture, a major soft tissue component, existing spinal cord or cauda equina compression, and neuropathic pain. There are contradictory outcomes in studies reporting pain control rates and time to pain reduction when comparing stereotactic ablative radiotherapy versus conventional fractions. The ideal ablative radiotherapy schedule to treat BM remains to be defined. Physical activity and rehabilitation should be included in the multidisciplinary treatment of BM, with specific adaptations to improve the patient's condition and minimise risks. Abstract: In patients with bone metastases (BM), radiotherapy (RT) is used to alleviate symptoms, reduce the risk of fracture, and improve quality of life (QoL). However, with the emergence of concepts like oligometastases, minimal invasive surgery, ablative therapies such as stereotactic ablative RT (SABR), radiosurgery (SRS), thermal ablation, and new systemic anticancer therapies, there have been a paradigm shift in the multidisciplinary approach to BM with the aim of preserving mobility and function survival. Despite guidelines on using single-dose RT in uncomplicated BM, its use remains relatively low. In uncomplicated BM, single-fraction RT produces similar overall and complete response rates to RT with multiple fractions, although it is associated with a higher retreatment rate of 20% versus 8%. Complicated BM can be characterised as the presence of impending or existing pathologic fracture, a major soft tissue component, existing spinal cord or cauda equina compression and neuropathic pain. The rate of complicated BM is around 35%. Unfortunately, there is a lack of prospective trials on RT in complicated BM and the best dose/fractionation regimen is not yet established. There are contradictory outcomes in studies reporting BM pain control rates and time to pain reduction when comparing SABR with Conventional RT. While some studies showed that SABR produces a faster reduction in pain and higher pain control rates than conventional RT, other studies did not show differences. Moreover, the local control rate for BM treated with SABR is higher than 80% in most studies, and the rate of grade 3 or 4 toxicity is very low. The use of SABR may be preferred in three circumstances: reirradiation, oligometastatic disease, and radioresistant tumours. Local ablative therapies like SABR can delay change or use of systemic therapy, preserve patients' Qol, and improve disease-free survival, progression-free survival and overall survival. Moreover, despite the potential benefit of SABR in oligometastatic disease, there is a need to establish the optial indication, RT dose fractionation, prognostic factors and optimal timing in combination with systemic therapies for SABR. This review evaluates the role of RT in BM considering these recent treatment advances. We consider the definition of complicated BM, use of single and multiple fractions RT for both complicated and uncomplicated BM, reirradiation, new treatment paradigms including local ablative treatments, oligometastatic disease, systemic therapy, physical activity and rehabilitation.